Global Applications of Culturally Competent Health Care: Guidelines for Practice (Springer International Publishing, 2018)
This book is unique in its global approach to applying the Guidelines for Culturally Competent Nursing Practice that were recently endorsed by the International Council of Nurses (ICN) and distributed to all of its 130 national nursing associations. The purpose of this book is to illustrate how these guidelines can be put into clinical practice and to show how practitioners from different countries with diverse populations can implement them. The first chapter provides the conceptual basis for Culturally Competent Health Care and describes how the guidelines were developed. Each of the next 10 sections presents a chapter describing a specific guideline followed by three or four chapters with detailed case studies to illustrate how the guideline was implemented in a particular cultural setting. All case studies follow a similar format and are written by international authors with clinical expertise and work experience in the culture being presented. This book will be useful for advanced practice nurses, healthcare students, clinicians, administrators, educators, researchers, and those who provide community health or population-based care. .